2014
DOI: 10.1136/annrheumdis-2014-205383
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in women with rheumatoid arthritis: influence of disease activity and medication

Abstract: TTP in RA is longer if patients are older or nulliparous, have higher disease activity, use NSAIDs or use prednisone >7.5 mg daily. Preconception treatment strategies should aim at maximum suppression of disease activity, taking account of possible negative effects of NSAIDs use and higher prednisone doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
2
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(103 citation statements)
references
References 37 publications
4
85
2
12
Order By: Relevance
“…Similarly, untreated asthma significantly prolongs time to pregnancy and reduce fertility mainly because of systemic inflammation 21 . The same applies to untreated rheumatoid arthritis 22 . It is likely that the increased time to pregnancy in these disorders is biological rather than behavioural 15 .…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, untreated asthma significantly prolongs time to pregnancy and reduce fertility mainly because of systemic inflammation 21 . The same applies to untreated rheumatoid arthritis 22 . It is likely that the increased time to pregnancy in these disorders is biological rather than behavioural 15 .…”
Section: Discussionmentioning
confidence: 96%
“…Finally, mainly based on studies in oncology and in animal models, it has been suggested that prior treatment with MTX is associated with impaired fertility [12]. However, in a prospective cohort study on RA and fertility, prior MTX treatment did not affect TTP [9]. Furthermore, short-term MTX treatment had no impact on the ovarian reserve in patients with RA [13].…”
Section: Fertility In Patients With Ramentioning
confidence: 93%
“…Clowse et al [8] reported that 36% of patients with RA had difficulties in conceiving at least once during their reproductive life span. In the Pregnancy-induced Amelioration of Rheumatoid Arthritis (PARA) study, a prospective Dutch cohort study on RA and pregnancy [9], it was shown that 42% of patients with RA did not conceive within 1 year or at all during the follow-up period of that study. For comparison, in the general population, the median prevalence of subfertility defined as TTP of >12 months is 9%, with a range of 3.5e24.2% depending on the geographic area [10,11].…”
Section: Fertility In Patients With Ramentioning
confidence: 98%
See 1 more Smart Citation
“…Good disease control is of obvious benefit to the mother but it also reduces adverse fetal and neonatal outcomes as well as improving fertility. 15 A 2013 meta-analysis showed that women who conceive with active inflammatory bowel disease have a higher rate of active disease during pregnancy (46-55%) than those who conceive while in remission (23-29%). 16 Similarly, systemic lupus erythromatosis flares during pregnancy are more common in those with active disease at conception.…”
Section: Inflammatory and Autoimmune Conditionsmentioning
confidence: 99%